Inclusive Services for Children and Families From CaLD Backgrounds in an Australian Context. (19th February 2014) - Sims, Margaret; Targowska, Anna; Kulisa, Judy; Teather, Susan
The current Australian government is proposing an agenda focused around social inclusion in an attempt to address the complex issues associated with inequality evident in this country. Despite valiant attempts, many agencies struggle to offer inclusive services, particularly to families who have migrated to Australia from culturally and linguistically diverse (CaLD) backgrounds. In this study, we surveyed a range of programs identified by key informants as offering inclusive service delivery with the aim of identifying those aspects of their practice they believed facilitated successful inclusion. We then attempt to position our findings within recently emerging critiques of the concept of social inclusion, of which our participants appeared unaware. This critique addresses the fundamental purpose of social inclusion, and the strategies commonly used to achieve it, arguing that these are based on a deficit approach that positions those who are excluded as "other." In identifying those who are excluded as "other" and attempting to include them into a hegemonic idea of civil society as functioning citizens, are agencies actually being racist?